Crying Unsettled and disTressed Infants Effectiveness Study of osteopathic care (CUTIES trial): Pragmatic randomised superiority trial protocol. (December 2020) - Carnes, D.; Bright, P.; Brownhill, K.; Carroll, K.; Engel, R.; Grace, S.; Vogel, S.; Vaucher, P.
Abstract: Background: Infants who excessively cry, are distressed and unsettled can have a marked impact on family life. One form of support is manual therapy and osteopathic care. There is, however, limited research and debate about the effectiveness of manual therapy and osteopathic care for these infants. Aim: To evaluate the effectiveness of osteopathic light touch manual therapy care for excessively crying, unsettled and distressed infants. Method: We propose a two-arm pragmatic randomised controlled trial, 112 infants will be randomised to either: (i) Specific osteopathic light touch manual therapy with best practice advice and support or, (ii) Non-specific light touch with best practice advice and support. Parents will be blinded to group allocation. Population: Healthy infants under 10 weeks old, reported by their parents as excessively crying, fussing, unsettled, distressed and difficult to console using the Rome IV criteria (>3 hours of crying per day, for 3 days or more, for 1 week or more). Infants with diagnosed health conditions for which they are receiving medical treatment or who are unsuitable for osteopathic care will be excluded from the study. Outcomes: The primary outcome is reduced infant mean crying time over 14 days, collected via parent reported diaries. Secondary outcomes are: (i) Parental self-efficacy, (ii) Parent perceived global improvement, (iii) Satisfaction and experience with treatment, (iv) Adverse events, and (v) Direct cost. Discussion: The results from this study will provide information that osteopaths, other health care professionals and parents can use to inform their decisions about treatment choices.